2018
DOI: 10.1007/s00894-018-3861-y
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity, stereoselectivity, and molecular mechanism of [3 + 2] cycloaddition reactions between 2-methyl-1-nitroprop-1-ene and (Z)-C-aryl-N-phenylnitrones: a DFT computational study

Abstract: Reaction paths for [3 + 2] cycloaddition (32CA) between 2-methyl-1-nitroprop-1-ene and (Z)-C-aryl-N-phenylnitrones were explored in detail at the B3LYP/6-31G(d) level of theory. All of the 32CA processes considered were found to be initiated by the attack of the most nucleophilic oxygen atom in the nitrone molecule on the most electrophilic carbon atom (Cβ) in the nitroethylene moiety. This type of interaction favors the formation of 4-nitro-substituted cycloadducts. Additionally, based on a molecular electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Such molecular complexes have been recently detected for 32CAs of disubstituted nitrones. [42][43][44] The molecular complexes (MCs) for present study were found to be enthalpic in nature with ∆H values of -6.7, -7.4, -4.0 and -1.5 kcal* mol -1 in gas phase and -0. The gas phase activation energy of TSox is lower than that of TSon, TSmx and TSmn by 1.5, 0.8 and 2.3 kcal mol -1 .…”
Section: Study Of the Energy Profile Associated With The 32ca Betweenmentioning
confidence: 64%
“…Such molecular complexes have been recently detected for 32CAs of disubstituted nitrones. [42][43][44] The molecular complexes (MCs) for present study were found to be enthalpic in nature with ∆H values of -6.7, -7.4, -4.0 and -1.5 kcal* mol -1 in gas phase and -0. The gas phase activation energy of TSox is lower than that of TSon, TSmx and TSmn by 1.5, 0.8 and 2.3 kcal mol -1 .…”
Section: Study Of the Energy Profile Associated With The 32ca Betweenmentioning
confidence: 64%
“…The Berny analytical gradient optimization approach was employed to optimize stationary points along the potential energy surface of 32CA reactions at the B3LYP/6-311++G(d,p) level [43,44]. Previous studies have supported the use of the B3LYP functional as a reliable and accurate approach for several 32CA reactions [6,[45][46][47]. Frequency calculations of the optimized TSs established the existence of one imaginary frequency, whereas the absence of an imaginary frequency for the local minimum was confirmed.…”
Section: Methodsmentioning
confidence: 97%
“…The Berny analytical gradient optimisation approach was used at the MPWB95/6-311++G (d,p) level for the optimization of the stationary points along the potential energy surface of the 32CA reactions [28,29]. The use of MPWB95 functional in the analysis of 32CA reaction has been shown to be a reliable and accurate approach [20,21,[30][31][32][33][34]. The optimized TSs' frequency computations revealed the existence of a single imaginary frequency, while the disappearance of imaginary frequencies was shown to be the local minimum.…”
Section: Methodsmentioning
confidence: 99%